The PreProcessor module for the ATLAS Tile calorimeter at the HL-LHC - Valero, A.; Carrió, F.; Fiorini, L.; Cervelló, A.; Hernandez, D.; Ruiz Martinez, A. (Frontiers in Detector Science and Technology, 2023)
The Large Hadron Collider (LHC) has played a crucial role in advancing our understanding of fundamental physics. With the discovery of the Higgs boson in 2012, the ATLAS and CMS experiments have made significant progess in studying its properties and searching for new physics beyond the Standard Model. To maintain and expand the LHC's discovery potential, the High-Luminosity LHC (HL-LHC) project is planned as a major upgrade. As part of this upgrade, the ATLAS experiment has developed a comprehensive roadmap for upgrades, including the installation of new detector components and advancements in data acquisition and processing systems. A crucial component of these enhancements involves the complete replacement of the ATLAS central Tile hadronic calorimeter readout electronics. This upgrade aims to optimize the system's ability to handle higher data rates and improve its resilience to radiation. Through these comprehensive improvements, the ATLAS experiment aims to meet the requirements and seize the opportunities presented by the HL-LHC era. This paper presents the design and architecture of the TilePPr (Tile PreProcessor) module, which serves as a crucial interface between the on-detector electronics and the central systems of the ATLAS experiment, including Data Acquisition, Detector Control, and Trigger systems. The TilePPr module is based on the Advanced Telecommunications Computing Architecture (ATCA) and incorporates high-speed optical links, communication interfaces, and data processing capabilities. Through a series of certification tests, the module has demonstrated its compliance with industry standards and functional requirements, confirming its suitability for seamless integration into the ATLAS experiment during the HL-LHC phase.